ΔNp63α down-regulates c-Myc modulator MM1 via E3 ligase HERC3 in the regulation of cell senescence. Issue 12 (December 2018) - Chen, Yonglong; Li, Yimin; Peng, Yougong; Zheng, Xuan; Fan, Shijie; Yi, Yong; Zeng, Peng; Chen, Hu; Kang, Han; Zhang, Yujun; Xiao, Zhi-Xiong; Li, Chenghua
Abstract p63 and c-Myc are key transcription factors controlling genes involved in the cell cycle and cellular senescence. We previously reported that p63α can destabilize MM1 protein to derepress c-Myc, resulting in cell cycle progress and tumorigenesis. However, how the proteasomal degradation of MM1 is facilitated remains unclear. In the present study, we identified a novel E3 ligase, HERC3, which can mediate ubiquitination of MM1 and promote its proteasome-dependent degradation. We found that ΔNp63α transcriptionally up-regulates HERC3 and knockdown of HERC3 abrogates ΔNp63α-induced down-regulation of MM1. Either overexpression of MM1 or ablation of HERC3 induces cell senescence, while knockdown of MM1 rescues cell senescence induced by deficiency of either ΔNp63α or HERC3, implicating the involvement of the ΔNp63α/HERC3/MM1/c-Myc axis in the modulation of cell senescence. Additionally, our Oncomine analysis indicates activation of the ΔNp63α/HERC3/MM1/c-Myc axis in invasive breast carcinoma. Together, our data illuminate a novel axis regulating cell senescence: ΔNp63α stimulates transcription of E3 ligase HERC3, which mediates ubiquitination of c-Myc modulator MM1 and targets it to proteasomal degradation; subsequently, c-Myc is derepressed by ΔNp63α, thereby cell senescence is modulated by this axis. Our work provides a new interpretation of crosstalk between p63 and c-Myc, and also sheds new light on ΔNp63α-controlled cell senescence and tumorigenesis.